Perjanjian Utang Piutang Yang Terdapat Klausula Memberatkan - Ahmad Fadly Haryadi; Nurfaidah Said; Marwah Marwah (Universitas Widya Gama Malang, 2023)
Legal protection for debtors in debt agreements that contain burdensome clauses. This study aims to analyze the binding legal force of a debt agreement that contains onerous clauses. This research is normative juridical, by analyzing the applicable laws and regulations and other literature related to this research. The results of this study indicate that the contents of the debt agreement deed containing a burdensome clause on the debtor can be considered invalid and null and void by law. The act of agreement in providing guarantees in the form of land plot certificates is not accompanied by an APHT as stipulated in Law Number 4 of 1996 concerning Mortgage Rights on Land and Objects (UUHT) which makes pledging the land invalid and the creditor does not have the right to the collateral. In addition, the contents of the agreement have violated the provisions of the vervalbeding principle, namely in Article 6 of the agreement deed. But it does not necessarily delete the principal agreement and the debtor's obligation to pay off his debt to the creditor because based on the provisions of Article 1338 of the Civil Code, agreements made by the law, namely the legal terms of the agreement in Article 1320 of the Civil Code apply as a law for the parties who make it. Errors in doing the agreement deed so that there is a clause burdening the debtor makes the authentic deed of the agreement turn into a private act by the provisions of Law Number 30 of 2004 concerning the Position of Notary Public (UUJN).